Exploring the Limits of Socioeconomic Characteristics in Explaining the Income of Hindu Communities in Areas Prone to Terrorism Issues - Ratini, Ni Ketut; Supetran, I Wayan (Jayapangus Press, 2025)
This study was motivated by the issue of terrorism in Indonesia, which has created uncertainty that has seriously impacted the economic welfare of the community, especially minority communities such as Hindus in Tambarana Village, Central Sulawesi. In this context, household income is an important indicator for understanding the economic resilience of vulnerable groups. This study aims to examine the influence of family dependents, family size, and work frequency on the income levels of Hindus affected by terrorism. This analysis can help to understand the income of the Hindu community as part of a larger ecosystem influenced by various socio-economic factors. This study uses a quantitative approach with a descriptive design and a cross-sectional model. Data collection techniques were carried out through a Likert scale questionnaire administered to 92 respondents selected using stratified random sampling. Data analysis was conducted using simple linear regression. The results indicate that the three independent variables do not have a significant impact on household income, with significance values above 0.05 and a model contribution of 1.9%. These findings suggest that demographic factors and work activities are insufficient to explain the income conditions of Hindu communities affected by terrorism. The study concludes that the economic resilience of minority communities is more influenced by structural, social, and cultural factors. Therefore, a multisectoral intervention strategy is needed that integrates cultural approaches, social support, and psychosocial recovery to strengthen the overall well-being of the community.